Effects of supplemental dietary chromium on yield and nutrient digestibility of laying hens under low temperature - Şahin, Kazım; Ertas, ON; Güler, T; Çiftçi, M (Tubitak Scientific & Technological Research Council Turkey, 2001)
This study was conducted to determine the effects of chromium picolinate (CrPi) added into diet containing 710.3 ppb chromium on yield and nutrient digestibility of laying hens at low temperature. Forty-six-week-old laying hens were randomly assigned to four groups of 30 hens per group. Treatment groups were fed different supplemental dietary chromium levels. Thus, hens were fed diets with no supplemental chromium (Control Group), 100 ppb of supplemental chromium (100 Group). 200 ppb of supplemental chromium (200 Group) and 400 ppb of supplemental chromium (400 Group). Diet chromium concentration was detected by graphite furnace atomic absorption spectroscopy. Body weight, feed efficiency and egg production increased both linearly (P<0.001) and quadratically (P<0.001) in laying hens at low temperature by supplemental dietary CrPi. However, feed intake, egg weight. egg shell thickness, egg shell weight, egg specific gravity and egg formation were not influenced by supplemental dietary CrPi (P>0.05). Digestibility of dry matter, organic matter, ether extract, crude protein, crude fiber and nitrogen free extract increased linearly (P<0.01) and quadratically (P<0.01) by supplemental dietary CrPi in laying hens under cold conditions (P<0.01). These results indicated that supplemental dietary CrPi increased yield and nutrient digestibility in laying hens at low temperature.
Düşük Çevre Sicakli?inda Yetiştirilen Yumurta Tavuklarinda Rasyona Katilan Kromun Verim ve Ham Besin Maddelerinin Sindirilme Derecesi Üzerine Etkisi
Keywords: low temperature; chromium; performance; digestibility; laying hens